ARTI PENTING PENDAFTARAN TANAH DALAM RANGKA PERLINDUNGAN HUKUM KEPEMILIKAN SERTIPIKAT HAK ATAS TANAH BAGI PEMILIK TANAH (STUDI DI DESA KALICILIK KABUPATEN DEMAK) - Pupi Eva Rahma Wahyuningsih, Ana Silviana, Herni Widanarti (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Land has a very important role. Increasing number of human population which isn’t matched by existing land can lead to disputes. That's because people are willing to do a variety of ways to achieve their goals. For this case, it’s necessary to have some rules to prevent the increasingly complex problems, especially on land. This research aims to determine the people at village of Kalicilik’s understanding how importance of the implementation of land registration, especially for legal protection to the land owners. What kind of motivations are owned by the people in the implementation of land registration. What kind of efforts have been carried out by the Land Office in order to achieve the implementation of the land certificate. The used method is juridical empirical’s method. Specifications research is descriptive analytical. contained in this research is that people in the Kalicilik’s village. Data analysis methods are systematically collected and collated and analyzed qualitatively. The results of the research and discussion that most of the people in the village are already know the importance of the implementation of land registration. By having a land certificate, will provide a sense of security because it can give legal certainty to landowners. However, there are still a few people in Kalicilik’s that have the legal awareness of it. The lack of awareness of the law in the village of Kalicilik mainly dues to economic factors (cost) and because of the lack’s of public knowledge about some land registration procedures correctly. it is influenced by the customs of the people who tend to prefer to use the agents in terms of land certificate’s proccedures. In that case, it takes the efforts of many sides like : land’s registration , village officials, the motivations indeed by the people’s sides to realize the orderly administration of land, especially for the land’s certificate.